Estimating Individual Ambiguity Aversion: A Simple Approach - Uri Gneezy; Alex Imas; John A. List (Center for Economic Studies and ifo Institute (CESifo), 2015)
We introduce a simple, easy to implement instrument for jointly eliciting risk and ambiguity attitudes. Using this instrument, we structurally estimate a two-parameter model of preferences. Our findings indicate that ambiguity aversion is significantly overstated when risk neutrality is assumed. This highlights the interplay between risk and ambiguity attitudes as well as the importance of joint estimation. In addition, over our stakes levels we find no difference in the estimated parameters when incentives are real or hypothetical, raising the possibility that a simple hypothetical question can provide insights into an individuals preferences over ambiguity in such economic environments.
Keywords: D01; D03; D81; 330; ambiguity aversion; experiments; estimation